Optimizing Engagement in Behavioral Parent Training: Progress Toward a Technology-Enhanced Treatment Model. Issue 2 (March 2021) - Jones, Deborah J.; Loiselle, Raelyn; Zachary, Chloe; Georgeson, Alexis R.; Highlander, April; Turner, Patrick; Youngstrom, Jennifer K.; Khavjou, Olga; Anton, Margaret T.; Gonzalez, Michelle; Bresland, Nicole Lafko; Forehand, Rex
Abstract: Low-income families are more likely to have a child with an early-onset Behavior Disorder (BD); yet, socioeconomic strain challenges engagement in Behavioral Parent Training (BPT). This study follows a promising pilot to further examine the potential to cost-effectively improve low-income families' engagement in and the efficiency of BPT. Low-income families were randomized to (a) Helping the Noncompliant Child (HNC; McMahon & Forehand, 2003), a weekly, mastery-based BPT program that includes both the parent and child or (b) Technology-Enhanced HNC (TE-HNC), which includes all of the standard HNC components plus a parent mobile application and therapist web portal that provide between-session monitoring, modeling, and coaching of parent skill use with the goal of improved engagement in the context of financial strain. Relative to HNC, TE-HNC families had greater homework compliance and mid-week call participation. TE-HNC completers also required fewer weeks to achieve skill mastery and, in turn, to complete treatment than those in HNC without compromising parent satisfaction with treatment; yet, session attendance and completion were not different between groups. Future directions and clinical implications are discussed. Highlights: Treatment engagement is a perennial challenge in children's mental health BPT engagement is particularly difficult for low-income families Results suggest technology-enhanced BPT can improve some engagement outcomes Additional personalization of technology-enhanced BPT may further improve engagement